Information Risk and Cost of Debt in Emerging Markets: Evidence from Qatar - Aldamen, Husam; Saker, Shada; Abouelhemdiat, Samah; Abu Hassira, Eman (Asian Journal of Business and Accounting, 2017)
This study examines the impact of information risk on the cost of debt incurred by companies in Qatar, a vital country within the Gulf Co-operation Council (GCC) and Middle East region. The results suggest that information risk impacts debt pricing in Qatar. More specifically, there is a positive relationship between discretionary accruals and the cost of debt. This suggests that management uses discretionary accruals opportunistically to signal information about the company. However, the findings do not show that the cost of debt is affected by non-discretionary accruals. It is important to note that the reported results differ based on company size. Small companies, in particular, show a negative relationship between discretionary accruals and the cost of debt. This might indicate that discretionary accruals are used by these firms to inform about their performance and as a result creditors react by lowering the cost of debt. Keywords: Cost of Debt, Discretionary Accruals, Emerging Market, Firm Size, Non-Discretionary Accruals JEL Classification: M40, M41